Crisis, Urban Segregation and Social Innovation in Catalonia - Cruz, Helena; Rubén Martínez, Moreno; Blanco, Ismael (PARTECIPAZIONE E CONFLITTO, 2017)
This paper questions the contribution of social innovation to the capacity of disadvantaged communities to resist the effects of the 2008 financial crisis and its social repercussions. It does so on the basis of a study on the dynamics of urban segregation and social innovation in the context of the crisis in Catalonia (Spain). The study adopts a multi-method approach that combines statistical analysis of urban segregation dynamics in the 2001-2012 period; the mapping of social innovation practices across the region; and a cross-case comparison of six case studies. The paper highlights the structural and metropolitan character of urban segregation in the region, which has been significantly aggravated both by the crisis and the residential transformation that occurred during the years of the housing bubble. It also shows that social innovation practices are distributed very unevenly in spatial terms, being concentrated in middle-income areas with a tradition of social mobilisation. In summary, the paper states the limits of social innovation as a driver for socio-spatial cohesion in cities and stresses the need for stronger (redistributive) public policies.